The Impact of Remote Work on Organizational Productivity : Evidence from the Post-Pandemic Era - Ali Hassan al-Jasim; Fatima Abbas al-Dulaimi; Omar Mahmud al-Tikriti (Universitas Kristen Indonesia Toraja, 2024)
This paper investigates the effects of remote work on organizational productivity in the post-pandemic context. Using data from multinational companies in Asia and Europe, the study identifies critical factors such as technology adoption, employee well-being, and management practices that influence productivity outcomes.